Disease Activity Patterns in the First 5 Years After Diagnosis in Children With Ulcerative Colitis: A Population-Based Study. (6th October 2020) - Aloi, M; Bramuzzo, M; Norsa, L; Arrigo, S; Distante, M; Miele, E; Romano, C; Giobbi, C; Panceri, R; Cucchiara, S; Alvisi, P; ,
Abstract: Background: The aim of this study was to define clusters of activity in a population-based cohort during the first 5 years after diagnosis in children with ulcerative colitis [UC] and to identify early prognostic risk factors. Methods: All UC patients from the SIGENP IBD registry with a complete follow-up of at least 5 years were included. Active disease was defined every 6 months in the presence of at least one of the following: clinical activity [Paediatric Ulcerative Colitis Activity Index ≥ 35]; endoscopic activity [Mayo score ≥ 1]; faecal calprotectin > 250 µg/g; hospitalization; surgery; or treatment escalation. Formula-based clusters were generated based on four published questionnaire-based activity patterns in adults, plus one additional cluster. Results: In total, 226 patients were identified. Forty-two [19%] had moderate–severe chronically active disease, 31 [14%] chronic–intermittent, 75 [33%] quiescent, 54 [24%] active disease in the first 2 years after the diagnosis, then sustained remission, and 24 [11%] a remission in the first 2 years then an active disease. Mild disease onset along with a lower clinical severity not requiring the use of corticosteroids at 6 months were related to a quiescent disease course at the next follow-up (logistic model area under the curve 0.86 [95% confidence interval 0.78–0.94]; positive predictive value 67%; negative predictive value 70%). Eight per cent of patients needed surgery, none in the quiescent group [ p  = 0.04]. Conclusions: More than one-third of children with UC present with a chronically active or intermittent course during the first 5 years of follow-up. A significant group of patients has active disease in the first 2 years and then sustained remission. Interestingly, after initial treatment, one-third of patients have well-controlled disease throughout.